Lie Ideals and Jordan Ɵ-Centralizers of Prime Rings - Majeed, Abdulrahman H; Meften, Mushreq I (Al-Nahrain Journal of Science, 2011)
The main purpose of this paper is to extend the result of B.Zalar about centralizers to Ɵ-centralizers on Lie ideals.